Efficacious bioconversion of waste walnut shells to xylotetrose and xylopentose by free xylanase (Xy) and MOF immobilized xylanase (Xy-Cu-BTC) - Kaushal, Jyoti; Arya, Shailendra Kumar; Khatri, Madhu; Singh, Gursharan; Izyan Wan Azelee, Nur; Rajagopal, Rajinikanth; Woong Chang, Soon; Ravindran, Balasubramani; Kumar Awasthi, Mukesh (Bioresource technology, 2022)
[Display omitted] •Xylanase (Xy) extracted from Bacillus pumilus bacterial strain was partially purified.•Production of Cu-BTC MOF was done at room temperature.•Xy was immobilized onto Cu-BTC MOF to form blue crystals of Xy-Cu-BTC.•Xylan was extracted from waste walnut shell.•Bioconversion of xylan to xylooligosaccharides by free and immobilized enzyme system. This study uses a cost effective and efficient method for production of higher DP (degree of polymerization) Xylooligosaccharides (XOS) from xylan extracted from the waste walnut shells. Copper based metal organic framework (Cu-BTC MOF) was prepared for immobilization of free xylanase (Xy) enzyme by green synthesis method. Both free and immobilized xylanase (Xy-Cu-BTC) were able to cause the bioconversion of xylan (87.4% yield) into XOS. Predominant production of xylotetrose (X4) and xylopentose (X5) was observed for both the methods. Percentage XOS conversion for free enzyme (Xy) was found to be 4.1% X4 and 60.57% X5 whereas these values increased in case of immobilized system where 11.8% X4 and 64.2% X5 were produced. Xylose production was minute in case of immobilized xylanase 0.88% which makes it a better method for XOS production free from xylose interference. Xy-Cu-BTC MOF can hence be used as an attractive alternative for pure XOS production.